Determinants of retinopathy of prematurity: A prospective observational study from Tertiary Care Teaching Hospital from North India - Gupta, Ashok K; Pandita, Neerul; Gupta, Surbhi; Sharma, Ashok K (Indian Journal of Child Health, 2014)
Objective: This prospective observational study was designed to evaluate the point prevalence as well as various risk factors associated with retinopathy of prematurity (ROP) in preterm/low birth weight (LBW) babies